Further studies on the Bracon hebetor-brevicornis-complex (Hymenoptera: Braconidae) by paper chromatography. - Chawla, S. S.; Subba Rao, B. R. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The technique of paper chromatography has been used to clear the existing confusion on the identities of Bracon brevicornis Wesmael and Bracon hebetor Say. It has been shown that there do exist differences in the amino acid constituents in three Bracon forms studied. B. brevicornis contained twelve amino acidsserine, glycine, hydroxyproline, histidine, valine, threonine, norleucine, methione, proline, leucine group and two unidentified amino acids whereas B. hebetor had serine, glycine, hydroxy proline, valine, threonine, norleucine, alanine, methione, proline, leucine group and two unidentified spots. Only eleven amino acids could be detected in Bracon gelechiae. These were serine, glycine, hydroxyproline, valine, threonine, alanine, methione, leucine group and two unidentified spots.